Photonic integrated circuit testbench - Mei, Ting. (2008)
In this project, we set up a test bed for photonic integrated circuits. The system can be used to measure several primary properties of photonic integrated circuit, such as I-V, L-I, optical spectrum, optical gain or loss and polarization dependence. The system can provide the electric bias for three channels simultaneously, e.g. suitable for the testing of integrated circuits. And we set up a polarized photoluminescence (PPL) test system for analyzing the mechanism of Argon ICP-enhanced QWI for fabricating the integrated optoelectronics devices. The cap material and doping effect was investigated for the Argon ICP-enhance QWI in InGaAs(P)/InP quantum well structure by the PPL test system. The InP cap is better than the InGaAs cap as more point defects can be accumulated in the cap layer, which promote the QWI by enhance the diffusion lengths of group V and group III sublattices. And the Zn highly doped p-InP is superior to the n- and i-InP with both high diffusion lengths of group V and group III sublattices during interdiffusion.